In search of a paradox of redistribution analysis of fiscal redistribution in high-income countries - David P. Coady (Luxembourg Income Study (LIS), 2023)
The last decade has seen a sharp increase in interest in the possible existence of a Paradox of Redistribution (PoR) whereby narrow targeting of social transfers aimed at increasing their redistributive (poverty) impact has the perverse effect of increasing poverty over the medium term due to decreasing public support for such spending. However, empirical support for the existence of a PoR has been mixed. We revisit this issue using harmonized LIS household survey data covering recent decades. Our analysis is embedded in the standard social welfare framework, which allows for an integrated and transparent evaluation of FR, making explicit the value judgements necessarily inherent in such analyses. Our results support recent findings that FR has increased over the last four decades, although we do not find support for some recent results that FR decreased since 1995. While we find strong support for a PoR for social insurance transfers (dominated by pension transfers), we find little support in the context of social assistance transfers. We argue that, in the context of social assistance, more detailed country-specific studies of the underlying political and economic dynamics are needed to adequately determine the existence or otherwise of a PoR. Our high-level analysis can, however, help to identify possible candidates for such country case studies.
Keywords: D31; D63; H23; I38; P43; 330; Inequality; poverty alleviation; social welfare policy; redistribution; progressivity; targeting; paradox of redistribution